p-Selective (sp(2))-C-H functionalization for an acylation/alkylation reaction using organic photoredox catalysis - Pandey, Ganesh; Tiwari, Sandip Kumar; Singh, Bhawana; Vanka, Kumar; Jain, Shailja (Chemical Communications, 2017)
p-Selective (sp(2))-C-H functionalization of electron rich arenes has been achieved for acylation and alkylation reactions, respectively, with acyl/alkylselenides by organic photoredox catalysis involving an interesting mechanistic pathway.